Description a new species of Nemacerota Hampson, [1893] (Lepidoptera: Thyatiridae) from the Xizang Autonomous Region, China - Da, Wa; Ronkay, László; Han, Huilin (Zootaxa, 2020)
A new species of Nemacerota Hampson, [1893], N. paizhenensis sp. n., is described from the Xizang Autonomous Region (= Tibet), China. The male adult and the genitalia of the new species are illustrated and compared with its most similar species: N. inouei László, Ronkay, Ronkay & Witt, 2007 and N. pectinata (Houlbert, 1921); an identification key and distribution map for all Chinese Nemacerota species are provided.